Raw material procurement at Abrigo do Poço Rock shelter (Central Portugal) - Pereira, Telmo (2021)
Abrigo do Poço is a rock shelter located in the karstic canyon of Ribeira das Chitas in the River Lis basin (Central Portugal). The site has an Epipaleolithic occupation overlying a Solutrean occupation. Despite the multiple available resources in the vicinity, the main activity during the Upper Paleolithic occupation seems to have been the exploitation of a small chert outcrop located right above it. This outcrop extends in patches throughout the vicinity due to the combination of tectonic activity and fluvial erosion that results in multiple canyons. Interestingly, the outcrop above the site is one in which the chert is less expressive, probably due to exhaustion during the Solutrean, during which the site was used to heat-treat chert for the production of blades and, especially, bifacial points. The chert from this site has different colors, patterns and textures due to internal variability and to external agents (tectonic, patina). Here we present the macroscopic and geochemical characteristics of this outcrop throughout the valley and discuss the issue of potentially misleading interpretations when only one of these approaches is used.